Optical properties and surface dynamics analyses of homojunction and hetrojunction Q/ITO/ZnO/NZO and Q/ITO/ZnO/NiO thin films - Solaymani, Shahram; Ţălu, Ştefan; Beryani Nezafat, Negin; Dejam, Laya; Shafiekhani, Azizollah; Ghaderi, Atefeh; Zelati, Amir (Results in physics, 2021)
•Optical properties of homojunction and hetrojunction Q/ITO/ZnO/NZO and Q/ITO/ZnO/NiO thin films investigated.•The 3-D AFM micrographs permitted detailed analysis of the micromorphology of surface’ samples.•The stereometric analysis allowed quantifying morphological changes in the local regions at the naonometer scale of the samples.•The surface texture characteristics permitted a better understanding of the surface topography of the samples. The aim of the present study is to verify how alternations of annealing temperatures modify optical and micromorphological properties of n-ZnO/p-NZO and n-ZnO/p-NiO multilayers. As can be seen, the optical analysis of homojunctions and hetrojunction thin films shows a red shift by increasing annealing temperature which means that annealing can shift absorption edge coefficient to the lower values of energies. Also, the effective parameters on optical properties of homo- and hetrojunction thin films such as optical band gap, Urbach energy, steepness parameter, and skin depth have been studied by their transmittance spectra. Moreover, the micromorphology of n/p ZnO homo- and heterojunctions transparent diodes have been studied by atomic force microscopy in combination with modern image processing techniques. The nano scaled stereometric analysis provides significant insights into the influence of preparation process on surface texture geometry. According to the results extracted from AFM micrographs by MountainsMap® software, it is observed that Q/ITO/ZnO/NZO sample with 300 °C annealing temperature has the normal distribution of peaks with the highest percentage of isotropy. In addition, it is observed that Q/ITO/ZnO/NiO with 500 °C annealing temperature has the most regular topography.